THU0732-HPR Enhanced management of ankylosing spondylities through guangdong internet hospital in china:a randomized, controlled trial. (15th June 2017) - Zhengping, H; Tianwang, L; Zhixiang, H; Xia, P; Lihua, Z; Yukai, H; Xiaoyan, Y; Meng, L; Xuechan, H; Yunqing, W; Xumian, L; Yao, T
Abstract : Background: Ankylosing Spondylitis (AS) is a kind of common chronic disease.Guangdong Internet Hospital is China's first officially recognized network hospital and the government encourage development of telemedicine in the country. Increasing research evidences support the efficacy of telemedicine in management of chronic diseases. However, There are still few researches about AS management by using telemedicine. Objectives: We here conducted a 6-month randomized, controlled trial to evaluate the feasibility and efficacy of Guangdong Internet Hospital in AS management. Methods: A total of 102 AS patients were randomly divided into two groups: standard care (ST) group or standard care with Network-Enhanced Management (ST-NEM) group. NEM enhanced disease management including cognition of the disease, medication monitoring, behavioral management and psychotherapy. Individuals were assessed by using several tools at baseline and 6 months later: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for the disease acticity, Ankylosing Spondylitis Functional Index (BASFI) for the functional limitation, the Zung Self-Rating Anxiety Scale (SAS) and the Zung Self-Rating Depression Scale Zung (SDS) for the psychological status, Pittsburgh sleep quality index (PSQI) for the sleep quality, and SF-36 for the general health status. In addition, we made a satisfaction survey about the network platform in the management of the disease. Both group received the same medications during the period. There were no significant differences in baseline demographic and clinical characteristics between the two groups. Results: After 6 month, 91 patients completed the trial. BASFI (1.75±0.73 vs. 2.04±0.69, P=0.026), SAS (28.12±3.22 vs. 39.56±4.61, P=0.022), SDS (26.51±6.34 vs. 32.12±6.34, P=0.031), PSQI (3.31±0.46 vs. 4.79±0.54, P=0.019) and SF-36 (SF-36M: 54.24±9.66 vs. 61.41±8.56, P=0.014; SF-36P: 63.42±11.08 vs. 68.98±10.46, P=0.032) were significantly lower in ST-NEM group than ST group after 6 months. There was no significant difference in BASDAI (2.66±0.91 vs. 2.75±0.75, P=0.068) between the two groups. Individuals assigned to the ST-NEM group reported significantly improvement in functional limitation, psychological status, sleep quality and the general health status. In addition, Guangdong Internet Hospital were widely accepted by the AS patients in disease management. Conclusions: Guangdong Internet Hospital showed potential feasibility and efficacy in AS management. AS patients may receive disease management through the netwrok platform conveniently and effectively, especially those in the remote areas of the country. The results may be important for clinical practice in disease management of AS by using telemedicine. References: Sinclair. 2015. Effectiveness and User Acceptance of Online Chronic Disease Management Interventions in Rural and Remote Settings: Systematic Review and Narrative Synthesis. Clinical Medicine Insights: Therapeutics: 43. Tu J, Wang C, Wu S. 2015. The internet hospital: an emerging innovation in China. The Lancet Global Health 3: e445-e6. Disclosure of Interest: None declared